Early interactions of pseudorabies virus with host cells: functions of glycoprotein gIII. - Zuckermann, F (1989)
Adsorption of mutants of pseudorabies virus (PrV) lacking glycoprotein gIII is slower and less efficient than is that of wild-type virus (C. Schreurs, T. C. Mettenleiter, F. Zuckermann, N. Snugg, and T. Ben-Porat, J. Virol. 62:2251-2257, 1988). To ascertain the functions of gIII in the early interactions of PrV with its host cells, we compared the effect on wild-type virus and gIII- mutants of antibodies specific for various PrV proteins. Although adsorption of wild-type virus was inhibited by polyvalent antisera against PrV as well as by sera against gIII and gp50 (but not sera against gII), adsorption of the gIII- mutants was not inhibited by any of these antisera. These results suggest that, in contrast to adsorption of wild-type PrV, the initial interactions of the gIII- mutants with their host cells are not mediated by specific viral proteins. Furthermore, competition experiments showed that wild-type Prv and the gIII- mutants do not compete for attachment to the same cellular components. These findings show that the initial attachment of PrV to its host cells can occur by a least two different modes--one mediated by glycoprotein gIII and the other unspecific. gIII- mutants not only did not adsorb as readily to cells as did wild-type virus but also did not penetrate cells as rapidly as did wild-type virus after having adsorbed. Antibodies against gIII did not inhibit the penetration of adsorbed virus (wild type or gIII-), whereas antibodies against gII and gp50 did. It is unlikely, therefore, that gIII functions directly in virus penetration. Our results support the premises that efficient adsorption of PrV to host cell components is mediated either directly or indirectly by gIII (or a complex of viral proteins for which the presence of gIII is functionally essential) and that this pathway of adsorption promotes the interactions of other viral membrane proteins with the appropriate cellular proteins, leading to the rapid penetration of the virus into the cells. The slower penetration of the gIII- mutants than of wild-type PrV appears to be related to the slower and less efficient alternative mode of adsorption of PrV that occurs in the absence of glycoprotein gIII.